2021
DOI: 10.1007/s11356-021-12613-6
|View full text |Cite
|
Sign up to set email alerts
|

Econometric analysis of COVID-19 cases, deaths, and meteorological factors in South Asia

Abstract: The pandemic has affected almost 74 million people worldwide as of 17 December 2020. This is the first study that attempts to examine the nexus between the confirmed COVID-19 cases, deaths, meteorological factors, and the air pollutant namely PM2.5 in six South Asian countries, from 1 March 2020 to 30 June 2020, using the advanced econometric techniques that are robust to heterogeneity across nations. Our findings confirm (1) a strong cross-sectional dependence and significant correlation between COVID-19 case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 75 publications
0
25
1
Order By: Relevance
“…That is, cities that had high air pollution and low wind speed had a higher transmission of the virus. Jain et al (2021) used advanced econometric techniques to examine the relationship between COVID-19 cases, deaths, and meteorological factors. COVID-19 cases and air pollutants were shown to have a statistically significant impact on COVID-19 deaths.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…That is, cities that had high air pollution and low wind speed had a higher transmission of the virus. Jain et al (2021) used advanced econometric techniques to examine the relationship between COVID-19 cases, deaths, and meteorological factors. COVID-19 cases and air pollutants were shown to have a statistically significant impact on COVID-19 deaths.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…The authors concluded that high temperature and humidity increase the transmission of COVID-19 and that this can also be applied to regions with higher transmission rates, where the minimum temperature is mostly above 21◦C and the humidity hovers at approximately 80% for months. Additionally, air pollutants (PM 2.5) exhibit significant negative and positive effects on the number of confirmed COVID-19 cases [ 10 ]. Other investigations have also used individual heterogeneity models as statistical methodologies to examine the relationships between meteorological variables and environmental pollution with respect to confirmed cases of COVID-19 and mortality, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are epidemiological and pathophysiological evidence suggesting an impact of emission levels on the upper and lower respiratory system in conjunction with various meteorological factors such as temperature, humidity, rainfall and atmospheric pressure (Braat et al, 2002;Muhling et al, 1984;Watson et al, 2006). Numerous studies have highlighted the relationship between meteorological parameters relating air quality and COVID-19 spread globally (Tosepu et al, 2020;Kumar, 2020;Ma et al, 2020;Guo et al, 2021;Jain et al, 2021;Shankar et al, 2021). Furthermore, meteorological variables have also been related to other diseases including cardiovascular diseases and respiratory diseases have also been reported (Bartzokas et al, 2004).…”
Section: Introductionmentioning
confidence: 99%